Професіоналізація порівняльної педагогіки в Україні: здобутки і виклики у вимірі педагогічної компаративістики у зарубіжжі - Локшина, Олена (Studies in Comparative Education, 2014)
У статті схарактеризовано ґенезу педагогічної компаративістики у зарубіжжі, прослідковано трансформацію її методологічних постулатів від лінійних запозичень у напрямі багатовимірного аналізу на основі системного, культурологічного, синергетичного та прогностичного підходів; підкреслено синхронізацію розвитку епістемологічної та інфраструктурної платформ педагогічної компаративістики, що засвідчує її професіоналізацію. Окреслено здобутки і виклики, що постають перед порівняльною педагогікою в Україні в процесі її становлення як окремої галузі педагогіки на тлі розвитку світової педагогічної компаративістики. В статье охарактеризован генезис педагогической компаративистики за рубежом, прослежена трансформация ее методологических постулатов от линейных заимствований в направлении многомерного анализа на основе системного, культурологического, синергетического и прогностического подходов; подчеркнута синхронизация развития эпистемологической и инфраструктурной платформ педагогической компаративистики, что свидетельствует о ее профессионализации. Очерчены достижения и вызовы, которые стоят перед сравнительной педагогикой в Украине в процессе ее становления как отдельной отрасли педагогики на фоне развития мировой педагогической компаративистики. The author analysis the genesis of pedagogical comparativistics abroad; traces the transformation of the comparative education methodological postulates from the linear borrowings towards a multidimensional analysis on the basis of the system, cultural, synergetic and prognostic approaches; underlines the synchronization of the development of the epistemological and infrastructure platforms of the comparative education, stressing its professionalization. In the article the professionalization is understood as the transformation of the comparative education into a separate area of pedagogical knowledge (with its subject, aim, tasks, methods and conceptual ideas) based on the infrastructural grounds (comprising professional associations, journals, and university courses). The author underlines the strong characteristics of the Ukrainian comparative education including the availability of several comparative education research centres; teaching of the «Comparative Education» course in a number of universities; publishing of the specialized journals, i.e. «Porivnyalno-Pedahohichni Studiyi» (The Comparative Education Studies, http://sce. udpu.org.ua) and «Porivnyalna Profesiyna Pedagogika (Comparative Professional Education, http://khnu.km.ua/angl/j/default.htm); conducting of the specialized events (by the research centres). The article contains a list of challenges (primarily methodological ones) facing the comparative education in Ukraine today. Among them are such open questions as the use of methods in the comparative education research; the format of comparison with the Ukrainian education; the format of a study result in order to be useful for the Ukrainian education; the selection of a topic for a research.